Synthesis of nanodispersed titanium dioxide via pH-controlled polymerization of titanium acid - Sadovskaya, Lyubov’ Yu.; Sviridova, Tatsiana V.; Morozova, Mariya V.; Sviridov, Dmitriy V. (Journal of the Belarusian State University. Chemistry, 2019)
The possibility of synthesis of highly photoactive nanosized titania employing ion exchange to exert control over polycondensation of titanium acid in aqueous medium has been demonstrated. The resultant spherical TiO2 nanoparticles exhibits extra high light-induced oxidation activity remaining for some time even after termination of UV illumination. The nanodispersed titania readily penetrate into the surface pores and can be used for deposition of photocatalytic coatings by impregnation technique.